The feeding of children from one to five years (London : His Majesty's Stationery Office)
1942-03 1942 1940s 24 pages 16 40. Crunch. 6 tablesp. Margarine. 1 1/2 teasp. Salt. 6 tablesp. Syrup. 12 cups Rolled Oats. Method : Beat margarine until soft : add syrup and work together. Mix rolled oats and salt and work gradually into margarine. Spread on shallow tin and bake in moderate oven until brown — 20 minutes approximately. Mark in squares and cut through when cold. MISCELLANEOUS. 41. Cocoa. 10 pints Milk. 3/4 lb. Sugar. 6 pints Water. 12 tablesp. Cocoa. Method : Blend cocoa with a little cold milk. Boil remainder of milk with water and sugar. Add blended cocoa and re-boil. Whisk and serve. 42. Porridge. 3 lbs. coarse or medium Oatmeal. 24 pints Water. 2tablesp. Salt. Method : Mix oatmeal, salt and a little water to a smooth paste. Bring water to boil and stir in paste. Cook for 1 1/2 - 2 hours, stirring frequently. Use a double boiler if possible. 43. Rusks. Cut slices of Bread 1/2 in. thick. Bake in cool oven until pale brown and crisp. This should be done after oven has been used for baking, etc. For variety, dip the rusks before baking into one of the following :— Cocoa, yeast extract, or jam or honey dissolved in milk or water. 44. Chocolate Spread. 1/2 lb. Cocoa. 1/4 lb. Margarine. 1/2 lb. Sugar. Milk. Method : Mix cocoa and sugar to thick cream with margarine, thinning down with a little milk. 45. Mock Lemon Curd. 4 oz. Custard Powder. 8 oz. Sugar. 1 quart Water. 1 tablesp. Margarine. 2 tablesp. Lemonade Crystals. 1 teasp. Bicarbonate of Soda. Method : Mix custard powder and lemonade crystals to a thin paste with cold water. Boil remainder of water and sugar and pour on to blended custard powder. Return to pan and bring to boil. Beat in the margarine and bicarbonate of soda. Cool and put into jars and cover. 46. Lentil Spread. 1 pint Lentils. 1/2 lb. Margarine. 1 large tablespoonful Yeast Extract. 4 breakfastcupfuls stale Breadcrumbs. Method : Wash and soak lentils. Put in pan with enough water to cover. Bring slowly to boiling point and cook until tender. Add remaining ingredients and bring to boiling point. Cool and pot. 127/NU/5/5/1/28